Optimization of bonding parameters in diffusion bonding of Cu10Sn-B4C composites produced by P/M method - Ada, Hakan; Özsoy, Serkan (National Library of Serbia, 2024)
In this study, bronze matrix and B4C reinforced composite materials were produced by the P/M method, and diffusion bonding processes were applied to these materials in the experimental setup created by the Taguchi method. In the bonding processes, it is assumed that the temperature required for diffusion will also be sufficient for the sintering of the samples, so an additional sintering process has not been performed on the specimens. Shear and microhardness tests and microstructural examinations were carried out to determine the material characterization. Microstructure examinations indicated that the powder metal specimens were properly sintered. In experimental studies, a decrease in microhardness and an increase in shear strength were observed as the temperature increased. With the increase in reinforcement rate, an increase in the shear strength of bonds and microhardness was observed. After the optimization process, the optimum result was detected in the bonding at 820?C temperature, 20 kg load, and 40 minutes duration in unreinforced bonding. At the end of the verification experiments, it was observed that the resistance value obtained in the experimental studies and the estimated value were negligible at 3.71%, and there was a 21.92% progress in shear strength compared to the initial parameter value.
Keywords: p/m; Chemical technology; bronze composite; TP1-1185; cu10sn; taguchi optimization; diffusion bonding